Beliefs about chelation among thalassemia patients - Trachtenberg, Felicia L (BioMed Central, 2012)
BACKGROUND: Understanding patients’ views about medication is crucial to maximize adherence. Thalassemia is a congenital blood disorder requiring chronic blood transfusions and daily iron chelation therapy. METHODS: The Beliefs in Medicine Questionnaire (BMQ) was used to assess beliefs in chelation in thalassemia patients from North America and London in the Thalassemia Longitudinal Cohort (TLC) of the Thalassemia Clinical Research Network (TCRN). Chelation adherence was based on patient report of doses administered out of those prescribed in the last four weeks. RESULTS: Of 371 patients (ages 5-58y, mean 24y), 93% were transfused and 92% receiving chelation (26% deferoxamine (DFO; a slow subcutaneous infusion via portable pump), 63% oral, 11% combination). Patients expressed high “necessity” for transfusion (96%), DFO chelation (92%) and oral chelation (89%), with lower “concern” about treatment (48%, 39%, 19% respectively). Concern about oral chelation was significantly lower than that of DFO (p<0.001). Self-reported adherence to chelation was not associated with views about necessity or concerns, but negatively correlated with perceived sensitivity to DFO (Sensitive Soma scale; r=−0.23, p=0.01) and side effects of oral chelation (r=−0.14, p=0.04). High ferritin iron levels, potentially indicating lower adherence, were found in 41% of patients reporting low necessity of oral chelation compared to 24% reporting high necessity (p=0.048). Concerns about treatment were associated with lower quality of life and more symptoms of anxiety and depression. CONCLUSIONS: Despite their requirement for multimodal therapy, thalassemia patients have positive views about medicine, more so than in other disease populations. Patients may benefit from education about the tolerability of chelation and strategies to effectively cope with side effects, both of which might be beneficial in lowering body iron burden. CLINICALTRIALS.GOV IDENTIFIER: NCT00661804